Mappe-monde geohydrographique, ou description generale du globe terreste et aquatique - Sanson, Nicolas, 1600-1667 (Honnold Mudd Library. Special Collections, 1684)
Double-hemisphere map, 97 x 57, engraved by Cordier. Presenté a Monseigneur le Dauphin par Hubert Iaillot a Paris. Janssonius-Goos type with California as an island like his map of 1656. The coast to the west is, however, without names and is labeled Terre de iesso ou Ieҫo and below Terre de la Compagnie. At the west end of this is the Destroict de Vriez. This seems to be a reissue of 409a. It was re-issued in 1691, 1695, 1696, and in later collections.